2018
DOI: 10.1021/acs.orglett.8b03356
|View full text |Cite
|
Sign up to set email alerts
|

Markovnikov-Selective Co(I)-Catalyzed Hydroboration of Vinylarenes and Carbonyl Compounds

Abstract: An NHC-supported Co(I) catalyst has been developed for selective Markovnikov hydroboration of vinylarenes under mild reaction conditions. The hydroboration allows highly selective synthesis of a wide range of secondary and tertiary alkyl boronates in excellent yields. Our protocol also enables hydroboration of aldehydes and ketones with diverse functional groups to access the corresponding borate esters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 95 publications
2
28
0
Order By: Relevance
“…[240] This transformation was the first example of asymmetric hydroboration of unactivated terminal alkenes. Also, several papers reported Co-, [244][245][246] Fe-, [247] and Nicatalyzed [248] "Markovnikov" boronations; however, the scope of these transformations were limited by styrene derivatives.…”
Section: Recent Advances In Alkene Hydroborationmentioning
confidence: 99%
“…[240] This transformation was the first example of asymmetric hydroboration of unactivated terminal alkenes. Also, several papers reported Co-, [244][245][246] Fe-, [247] and Nicatalyzed [248] "Markovnikov" boronations; however, the scope of these transformations were limited by styrene derivatives.…”
Section: Recent Advances In Alkene Hydroborationmentioning
confidence: 99%
“…A simple and commercially available Co(acac) 3 ( 14 ), precatalyst, in combination with NaO t Bu and PPh 3 was found to be efficient for Markovnikov selective hydroboration of alkenes with up to 97:3 selectivity. Very recently, Co(IMes) 2 Cl ( 15 ) [91] and Co(II) polymer ( 16 ) [92] were also reported for Markovnikov selective hydroboration of alkenes; the former was also capable of catalyzing additive-free hydroboration of carbonyls. In particular, an impressive TOF of up to 47,520 h −1 was reported by Zheng and co-workers, and this made it the most efficient catalyst for hydroboration of alkenes to date [92] (Scheme 2).…”
Section: Cobalt-catalyzed Hydroboration Of Alkenes and Co2mentioning
confidence: 99%
“…For example, we observed that the addition of PPh 3 as an ancillary ligand suppressed the formation of side products, such as ethylbenzene, and significantly increased the overall yield and regioselectivity for Markovnikov addition of styrene from 75:25 to as much as 94:6 [50]; Thomas [90] and Zheng [84] observed no reactivity in the absence of their NNN-based ligands. Furthermore, the addition of NaO t Bu or KO t Bu as an additive was an important component for catalysis as well; it was used to initiate catalysis presumably by activating the precatalyst and HBpin [93], though it should be noted that Geetharani’s N -heterocyclic carbene (NHC) supported Co(I) complex ( 15 ) [91] and Zheng’s NNN supported Co(II) complex ( 13 ) [84] could efficiently hydroborate alkenes under additive-free conditions.…”
Section: Cobalt-catalyzed Hydroboration Of Alkenes and Co2mentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports of a wide variety of metal catalysts from main group elements, including catalysts based on alkali or alkaline earth metals, namely, Al, Si, Ge, Sn, as well as rare earth metal catalysts such as those based on La and Yb, which have been used in the hydroboration of carbonyl compounds (Figure ). Transition metals such as Ti, Mn, Fe, Mo, Rh, Ru, Co, and Cu have also been used as the bases for developing catalysts. Notably, Hreczycho et al avoided the use of metal catalysts and reported the hydroboration of aldehydes under catalyst‐ and solvent‐free conditions; however, the reaction they reported required harsh conditions to be effective .…”
Section: Introductionmentioning
confidence: 99%